A Retrospective Analysis of COVID-19-infected Patients with Acute Hepatitis who Develop Acute Liver Failure in a Safety Net Hospital - Swapna Munnangi; Jagadish Akella; Jose R Russe-Russe; James Robert Pellegrini Jr.; Bhanu Sabbula; Rezwan F Munshi; Daniel Meshoyrer; Nourma Sajid; Alex Gutierrez; Elisa Szydziak (BMJ Open Gastroenterology)
Objective In early 2019, a new coronavirus called SARS-CoV-2 emerged and changed the course of civilization. Our study aims to analyze the association between acute liver failure (ALF) and mortality in patients infected with COVID-19. A retrospective analysis of 864 COVID-19-infected patients admitted to Nassau University Medical Center in New York was performed.Design ALF is identified by acute liver injury (elevations in liver enzymes), hepatic encephalopathy and an international normalised ratio greater than or equal to 1.5. These parameters were analysed via daily blood work and clinical assessment. Multivariate logistic regression model predicting mortality and controlling for confounders such as age, coronary artery disease, intubation, hypertension, diabetes mellitus and acute kidney injury were used to determine the association of ALF with mortality.Results A total of 624 patients, out of the initial 864, met the inclusion criteria—having acute hepatitis and COVID-19 infection. Of those 624, 43 (6.9%) patients developed ALF during the course of their hospitalisation and their mortality rate was 74.4%. The majority of patients with ALF were male (60.6%). The logistic model predicting death and controlling for confounders shows COVID-19 patients with ALF had a nearly four-fold higher odds of death in comparison to those without ALF (p=0.0063).Conclusions Findings from this study suggest that there is a significant association between mortality and the presence of ALF in patients infected with COVID-19. Further investigation into patients with COVID-19 and ALF can lead to enhanced treatment regimens and risk stratification tools, which can ultimately improve mortality rates during these arduous times.